Adjunctive Peony-Glycyrrhiza decoction for antipsychotic-induced hyperprolactinaemia: a meta-analysis of randomised controlled trials. Issue 1 (8th September 2018) - Zheng, Wei; Cai, Dong-Bin; Li, Hai-Yan; Wu, Yu-Jie; Ng, Chee H; Ungvari, Gabor S; Xie, Shan-Shan; Shi, Zhan-Ming; Zhu, Xiao-Min; Ning, Yu-Ping; Xiang, Yu-Tao
Abstract : Background: Hyperprolactinaemia is a common adverse effect of antipsychotics (APs). The results of Peony-Glycyrrhiza decoction (PGD) as a potentially useful adjunctive treatment for hyperprolactinaemia are inconsistent. Aim: This meta-analysis of randomised controlled trials (RCTs) examined the efficacy and safety of adjunctive PGD therapy for AP-induced hyperprolactinaemia. Methods: English (PubMed, Embase, Cochrane Library, PsycINFO) and Chinese (Chinese National Knowledge Infrastructure, Wanfang Data) databases were systematically searched up to 10 June 2018. The inclusion criteria were based on PICOS— P articipants: adult patients with schizophrenia; I ntervention: PGD plus APs; C omparison: APs plus placebo or AP monotherapy; O utcomes: efficacy and safety; S tudy design: RCTs. The weighted mean difference (WMD) and risk ratio (RR) along with their 95% CIs were calculated using Review Manager (RevMan) V.5.3 software. Results: Five RCTs (n=450) were included and analysed. Two RCTs (n=140) were double-blind and four RCTs (n=409) reported 'random' assignment with specific description. The PGD group showed a significantly lower serum prolactin level at endpoint than the control group (n=380, WMD: −32.69 ng/mL (95% CI −41.66 to 23.72), p <0.00001, I 2 =97%). Similarly, the superiority of PGD over the control groups was also found in the improvement of hyperprolactinaemia-related symptoms. No difference was found in the improvement of psychiatric symptoms assessed by the Positive and Negative Syndrome Scale (n=403, WMD: −0.62 (95% CI −2.38 to 1.15), p =0.49, I 2 =0%). There were similar rates of all-cause discontinuation (n=330, RR 0.93 (95% CI 0.63 to 1.37), p =0.71, I 2 =0%) and adverse drug reactions between the two groups. According to the Grading of Recommendations Assessment, Development and Evaluation approach, the level of evidence of primary and secondary outcomes ranged from 'very low' (14.3%), 'low' (42.8%), 'moderate' (14.3%), to 'high' (28.6%). Conclusions: Current evidence supports the adjunctive use of PGD to suppress elevated prolactin and improve prolactin-induced symptoms without significant adverse events in adult patients with AP-induced hyperprolactinaemia. High-quality RCTs with longer duration are needed to confirm these findings. Trial registration number: 42016037017.